2020
DOI: 10.1002/tox.23018
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid: A promising genoprotective and hepatoprotective bioactive compound against cyclophosphamide induced toxicity in mice

Abstract: Cyclophosphamide (CP) is a potent chemotherapeutic agent and is also known to interact with specific biological molecules and produce numerous side effects such as genotoxicity, neurotoxicity, reproductive toxicity and nephrotoxicity. CP induces genotoxicity by generating oxygen/nitrogen derived free radicals during chemotherapy and causes DNA damage. Hence, to overcome such side effects of chemotherapeutic agents antioxidants are recommended. Gallic acid (GA) a phenolic compound is commonly exists in variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The present study revealed high DNA damage in the CDDP-treated group (70 percent − 80 percent) (Fig. 4) compared to the control group (2 percent − 5 percent), as evidenced by the increased movement of DNA from the comet's head to the tail 59 . The ability of CDDP to cross-link with purine bases in DNA, producing DNA damage in malignant cells, has been related to its genotoxic potential.…”
Section: Nitric Oxide (No)mentioning
confidence: 48%
“…The present study revealed high DNA damage in the CDDP-treated group (70 percent − 80 percent) (Fig. 4) compared to the control group (2 percent − 5 percent), as evidenced by the increased movement of DNA from the comet's head to the tail 59 . The ability of CDDP to cross-link with purine bases in DNA, producing DNA damage in malignant cells, has been related to its genotoxic potential.…”
Section: Nitric Oxide (No)mentioning
confidence: 48%
“…Previous studies with gallic acid, a marker compound identified in both tested extracts, reported no mutagenic effects up to the concentration of 5000 µg/plate using the Ames test [ 44 ]. Additionally, gallic acid has been described as genoprotective and hepatoprotective [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid can have anti-inflammatory and antioxidant properties and has protective effects on the liver. 14,15 The Corni Fructus medicinal effect after processing is enhanced. 16 The iridoid glycosides have various pharmacological activities such as anti-tumor, anti-inflammatory, neuroprotection, among others.…”
Section: Discussionmentioning
confidence: 99%